2020
DOI: 10.1016/j.ijscr.2020.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Case report demonstrating abdominal tuberculosis presenting as an irreducible para-umbilical hernia

Abstract: Highlights Diagnosis of abdominal tuberculosis is challenging due to non-specific findings and clinical signs. A high index of suspicion of abdominal tuberculosis should be kept especially in endemic areas and for immune compromised patients who present with non-specific abdominal symptoms. Abdominal tuberculosis rarely presents as umbilical hernias with only 1 reported case in the literature. Routine histopathologic examination of herni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…It is a common problem in developing countries compromising around 5 percent of all cases of TB worldwide. 5 ATB is still a common entity in Indian subcontinent. Abdominal tuberculosis can involve any of the following abdominal sites: peritoneum, gastrointestinal tract, omentum, hepatobiliary tree, pancreas, perianal area, and lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a common problem in developing countries compromising around 5 percent of all cases of TB worldwide. 5 ATB is still a common entity in Indian subcontinent. Abdominal tuberculosis can involve any of the following abdominal sites: peritoneum, gastrointestinal tract, omentum, hepatobiliary tree, pancreas, perianal area, and lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…3 Anti-tuberculous therapy often responding poorly in long and multiple strictures and patients often require surgical intervention. 5 In surgical speciality clinics umbilical and inguinal hernias are seen very commonly. Detailed review of the reported cases of tuberculosis in umbilical and inguinal hernia demonstrates that they were diagnosed on intraoperative clinical findings and histopathological examination thereupon.…”
Section: Discussionmentioning
confidence: 99%